Iron-based phosphate positive electrode active material prepared by doping iron phosphate and preparation method and application thereof

CN118108201BActive Publication Date: 2026-10-27CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410098509.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2026-10-27
Estimated Expiration
2044-01-24

AI Technical Summary

Technical Problem

[0008]针对现有掺杂的铁基磷酸盐材料难于成功掺杂,难于满足高倍率、低温长循环应用要求等问题,本发明的目的在于,提供一种掺杂磷酸铁制备铁基磷酸盐正极活性材料(本发明也简称为铁基磷酸盐活性材料)的方法,旨在改善晶格掺杂效果和结构稳定性,进而改善制得的材料的高倍率、低温、长循环性能

Benefits of technology

[0065]本发明创新地预先将金属M对磷酸铁进行掺杂,随后再和其他的成分进行混合烧结,如此能够意外地实现协同,能够改善金属M对Fe位的晶格掺杂效果和稳定性,进而改善其高倍率、低温下的长循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118108201B_ABST
    Figure CN118108201B_ABST
Patent Text Reader

Abstract

The application belongs to the field of sodium ion battery materials, and particularly relates to a method for preparing an iron-based phosphate positive electrode active material by doping iron phosphate, wherein iron phosphate doped with a metal M is obtained in advance, and then the iron phosphate doped with the metal M is compounded with other raw materials for synthesizing an active material and is calcined to obtain the iron-based phosphate positive electrode active material; the metal M includes at least one of Ni, Ti, Mg, Mn, V, Al, Zr, Zn and Cr. The application also includes the material prepared by the method and application of the material. The application provides a brand-new front-end doping preparation process, which can unexpectedly improve long cycle effect of the prepared material at high rate and low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery materials technology, specifically relating to the field of positive electrode active materials for sodium-ion batteries. Background Technology

[0002] Among rechargeable batteries, lithium-ion batteries are quite mature in research and widely used in portable electronic devices and automobiles. With societal development, the demand for clean energy is increasing, and the market for large-scale energy storage is growing rapidly. However, the uneven distribution and insufficient reserves of lithium resources make it difficult to meet the requirements of large-scale energy storage. Sodium-ion batteries have a similar working principle to lithium-ion batteries, and sodium resources are widely distributed and abundant, making them a promising battery system for large-scale energy storage.

[0003] Currently, the main cathode systems for sodium-ion batteries include layered oxides, polyanionic compounds, Prussian blue, and their analogues. Among them, layered oxides have high specific capacity, but multiple phase transitions during cycling cause the structure to collapse easily, resulting in poor cycle performance. The crystal water problem of Prussian blue and its analogues is difficult to solve, and they are prone to gas generation at high potentials.

[0004] In contrast, polyanionic compounds possess a well-developed three-dimensional framework, thus exhibiting good cycle stability. Iron-based phosphates, in particular, offer resource advantages and are environmentally friendly, making them suitable for large-scale energy storage and the optimal choice for commercial sodium-ion battery cathode materials. However, iron-based polyanionic materials often have low electrical conductivity, requiring carbon modification to improve electronic conductivity. Taking lithium iron phosphate (LFP) as an example, surface carbon coating via glucose pyrolysis is a well-established process. Generally, a carbon coating of approximately 1–2% is sufficient to meet the electronic conductivity requirements of LFP. However, for iron-based polyanionic materials, the low sintering temperature and low degree of carbon graphitization result in poor conductivity.

[0005] In recent years, research on iron-based phosphate cathode materials has mainly focused on doping with trace metal elements to compensate for the poor conductivity of these materials. However, this has led to a problem: the choice of iron source in iron-based phosphates has primarily focused on iron phosphate, which has good product consistency. Choosing iron phosphate as the iron source requires additional phosphorus source for doping with trace metal elements, which is not conducive to atomic-level mixing of the dopant and the iron source, easily leading to the formation of impurity phases and a decline in electrochemical performance.

[0006] In addition, existing technologies have also provided some Fe-site doping ideas to address the problems faced by iron-based phosphate materials. For example, Chinese patent document CN114956031A discloses a method for preparing a sodium iron phosphate composite material of ferrophosphate type, specifically describing a process of mixing iron phosphate, sodium source, boron source, magnesium source, solvent, and dispersant in a certain proportion, spraying, and sintering to obtain the sodium iron phosphate composite material. Another example is Chinese patent document CN114725382A, which discloses a Mg-doped fluorinated sodium iron phosphate material for sodium-ion batteries and its preparation method, specifically describing the mixing of sodium bicarbonate, ferrous oxalate, sodium fluoride, ammonium dihydrogen phosphate, and magnesium source; followed by ball milling and sintering to obtain Mg-doped fluorinated sodium iron phosphate.

[0007] As can be seen above, existing technologies involve some doping modification approaches and can show good results at conventional room temperature and low rates. However, existing preparation methods mainly involve a one-pot back-end doping approach with Na, Fe, P, and other doping elements. This method is prone to problems such as difficulty in successful doping and unsatisfactory doping uniformity, making it difficult to meet the more demanding application requirements such as high rates, low temperatures, and long cycles. Summary of the Invention

[0008] To address the challenges of successfully doping existing iron-based phosphate materials and meeting the requirements for high-rate, low-temperature, and long-cycle applications, this invention aims to provide a method for preparing iron-based phosphate cathode active materials (also referred to as iron-based phosphate active materials) by doping with iron phosphate. This method aims to improve the lattice doping effect and structural stability, thereby enhancing the high-rate, low-temperature, and long-cycle performance of the prepared materials.

[0009] The second objective of this invention is to provide a method for preparing iron-based phosphate cathode active materials using doped iron phosphate and its applications.

[0010] A third objective of this invention is to provide a sodium-ion battery comprising an iron-based phosphate cathode active material prepared by doping with iron phosphate, and the cathode and cathode material thereof.

[0011] Most existing doped iron-based phosphate cathode active materials are prepared by one-pot mixing and sintering of iron, phosphorus, and sodium sources, or by mixing iron phosphate with sodium and dopant sources before sintering. While these downstream processes can achieve certain performance at low rates and room temperatures, they are insufficient for high-rate and low-temperature long-cycle applications. To address this issue, this invention provides the following improvement:

[0012] A method for preparing iron-based phosphate cathode active material by doping with iron phosphate involves first obtaining iron phosphate doped with metal M, and then combining it with other raw materials for synthesizing active material and calcining it to obtain the iron-based phosphate cathode active material.

[0013] The metal M includes at least one of Ni, Ti, Mg, Mn, V, Al, Zr, Zn, and Cr.

[0014] This invention innovatively demonstrates that pre-doping iron phosphate with metal M followed by mixing and sintering with other components can unexpectedly achieve synergy, improving the lattice doping effect of metal M on Fe sites, enhancing the stability of lattice doping, and thus improving the long-cycle stability of the prepared material at high rates and low temperatures.

[0015] In this invention, the pre-doping of iron phosphate with metal M is key to improving the high-rate, low-temperature, and long-range cycling stability of the final prepared material.

[0016] In this invention, the metal M-doped iron phosphate can be obtained based on known processes, or it can be obtained directly from recycled metal M-doped iron phosphate.

[0017] In a preferred embodiment of the present invention, a metal M source, a phosphoric acid source, and an iron source are co-precipitated and dried to obtain the metal M-doped iron phosphate.

[0018] In this invention, the metal M source and the iron source are water-soluble salts of their respective metal elements;

[0019] In this invention, the metal M source and iron source are derived from at least one leachate from minerals containing the elements and waste battery cathode materials.

[0020] In this invention, the phosphoric acid source is at least one of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate.

[0021] In this invention, the molar ratio of (M+Fe) / P in the metal source M, iron source, and phosphoric acid source is 0.95 to 1:1, and the molar percentage of M / (M+Fe) is 0.1 to 5 mol%, which can be further 1 to 3 mol%.

[0022] In this invention, the pH of the coprecipitation stage is 1–4, preferably 1.8–2.2. The coprecipitation process is carried out under stirring. Furthermore, the coprecipitation reaction time is preferably 3–6 hours, and more preferably 4–5 hours.

[0023] In this invention, after co-precipitation, solid-liquid separation and drying are performed (the drying method can be vacuum drying, and the processing temperature is less than or equal to 150°C) to obtain the metal M-doped iron phosphate.

[0024] In order to further improve the preparation advantages of the front-end doping process, a preferred method for obtaining metal M-doped iron phosphate is to perform thermal activation treatment on the co-precipitated and dried material at a temperature of 450-700℃ (preferably 500-600℃) to obtain the metal M-doped iron phosphate.

[0025] Preferably, the atmosphere for the thermal activation process is at least one of nitrogen and an inert gas;

[0026] Preferably, the thermal activation treatment time is 1 to 6 hours, and more preferably 3 to 4 hours;

[0027] Preferably, the co-precipitated and dried material is pre-activated and then thermally activated to obtain the metal M-doped iron phosphate.

[0028] Preferably, the atmosphere of the pre-activation stage is at least one of nitrogen and an inert gas;

[0029] Preferably, the temperature of the pre-activation stage is 300–400°C;

[0030] Preferably, the pre-activation stage lasts for 1 to 2 hours.

[0031] In this invention, iron phosphate doped with co-metal M and other raw materials are composite-calcined to obtain the iron-based phosphate positive electrode active material.

[0032] In this invention, the other raw materials include a sodium source. For example, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, an organic acid salt of sodium, and sodium phosphate.

[0033] In a preferred embodiment of the present invention, when the active material of iron-based pyrophosphate is prepared, a phosphorus source can be further added to other raw materials. The added phosphorus source can be at least one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate.

[0034] Another exemplifiable aspect of the present invention is that, when the synthesized iron-based phosphate is sodium ferric phosphate, a halogen source, such as a typical fluorine source, can be further added to the other raw materials.

[0035] In this invention, carbon sources are also permitted among the other raw materials.

[0036] In this invention, the carbon source can be a conventional water-soluble organic compound, and is more preferably at least one of glucose, citric acid, starch, ascorbic acid, cyclodextrin, and polyethylene glycol.

[0037] The amount of carbon source can be adjusted as needed. For example, the weight ratio of the carbon source to metal M-doped iron phosphate is 5-15%.

[0038] In this invention, the composite method is solid-phase composite, or liquid-phase composite followed by solvent removal treatment;

[0039] In this invention, the solvent in the liquid phase composite stage is an aqueous solvent, preferably a mixture of water and a water-organic solvent;

[0040] In this invention, the liquid-phase recombination stage is carried out with mechanical assistance;

[0041] In this invention, the mechanical auxiliary means is ball milling or sand milling;

[0042] In this invention, the solvent removal method is spraying.

[0043] In this invention, the calcination stage is carried out in a protective atmosphere, and further, the protective atmosphere includes at least one of nitrogen and an inert gas;

[0044] In this invention, the calcination temperature is 450-650℃, preferably 500-600℃;

[0045] In this invention, the calcination time at the calcination temperature is 4-14 hours, preferably 6-10 hours;

[0046] In this invention, the material is crushed after roasting.

[0047] In this invention, the crushing method is airflow crushing;

[0048] In this invention, the D50 of the crushed particles is controlled at 2-4 μm.

[0049] The present invention also provides a method for preparing iron-based phosphate cathode active materials by doping with iron phosphate using the method described above.

[0050] In this invention, based on the preparation method described above, the prepared material can be unexpectedly endowed with special physicochemical properties, and the material prepared by the method has excellent high-rate, low-temperature, and long-range cycling stability.

[0051] In this invention, the chemical formula of the prepared iron-doped iron phosphate cathode active material is, for example, Na. a Fe b M c (PO4) d (P2O7) e Where 0 < a < 5; 0 < b < 4; c is 0.01 to 0.05; 0 ≤ d < 4; 0 ≤ e < 4; where d and e are not both 0.

[0052] Preferably, a is 2 to 4, b is 1 to 3, c is 0.01 to 0.05, and d+e = 1 to 3;

[0053] Furthermore, the chemical formula for the iron-based phosphate positive electrode active material prepared by doping with iron phosphate is: Na₂Fe₂O₃. 1- c M c P2O7, Na4Fe 3-c M c (PO4)2P2O7, Na3Fe 2-c M c One or more of (PO4)P2O7.

[0054] In this invention, the iron-based phosphate positive electrode active material prepared by doping with iron phosphate is neutral in charge.

[0055] The present invention also provides an application of the iron-doped iron phosphate prepared by the above preparation method to prepare iron-based phosphate positive electrode active material, which is used as a positive electrode active material for preparing sodium-ion batteries.

[0056] In this invention, based on known principles and methods, the iron-based phosphate positive electrode active material prepared by doping iron phosphate as described in this invention can be used to prepare the desired sodium-ion battery and its positive electrode and positive electrode material.

[0057] The present invention also provides a positive electrode for a sodium-ion battery, comprising a current collector and a positive electrode material composited on its surface, wherein the positive electrode material comprises a positive electrode active material, and the positive electrode active material comprises an iron-based phosphate positive electrode active material prepared by the preparation method of the present invention by doping with iron phosphate.

[0058] In this invention, the positive electrode active material may also contain other active materials known in the industry. To further leverage the advantages of the positive electrode active material of this invention, the content of the iron-based phosphate positive electrode active material prepared by doping with iron phosphate is 20 wt% or more, preferably 60 wt% or more, and more preferably 90 wt% or more. Furthermore, it can be the iron-based phosphate positive electrode active material prepared by the method of this invention.

[0059] In this invention, the content of the positive electrode active material in the positive electrode material is above 60 wt.%, preferably 70 to 90 wt.%.

[0060] In this invention, the positive electrode material may also contain conductive agents and binders;

[0061] In this invention, the content of conductive agent and binder is less than 15 wt.%, preferably 5 to 10 wt.%.

[0062] The present invention also provides a sodium-ion battery, comprising a battery cell and an electrolyte for soaking the battery cell, wherein the battery cell comprises a positive electrode, a separator and a negative electrode sequentially composited, characterized in that the positive electrode is a positive electrode containing an iron-based phosphate positive electrode active material prepared by the preparation method described in the present invention by doping with iron phosphate.

[0063] In this invention, the sodium-ion battery, apart from the positive electrode active material described in this invention, may contain other known components and parts.

[0064] Beneficial effects

[0065] This invention innovatively pre-dops iron phosphate with metal M, and then mixes and sintersects it with other components. This unexpectedly achieves synergy, which can improve the lattice doping effect and stability of metal M on Fe sites, thereby improving its long-cycle stability at high rates and low temperatures. Attached Figure Description

[0066] Figure 1 The diagram shows the cycling performance of the material obtained in Example 1. Detailed Implementation

[0067] The present invention provides an optional method for preparing an iron-based phosphate cathode material, but its shortcomings include:

[0068] S1. Prepare iron phosphate doped with metal M in advance;

[0069] S2. Mixing: Mix sodium source, metal M-doped iron phosphate, phosphorus source, and carbon source according to the stoichiometric ratio in the molecular formula Na4Fe 3-c M c Weigh the raw materials (PO4)2P2O7 and mix them evenly to obtain the initial mixture;

[0070] S3, Sand milling: Add an appropriate amount of solvent to the initial mixture obtained in S1, control the solid content of the slurry to be 30%-50%, and then sand mill until the particle size D50 of the slurry is 0.2-0.4μm;

[0071] S4. Spraying: The slurry obtained in step S2 is spray-dried to obtain the precursor;

[0072] S5. Sintering: The precursor obtained in step S3 is sintered in an inert atmosphere, wherein the sintering temperature is 500-600℃ and the sintering time is 4-14h.

[0073] S6. Crushing: The material obtained in step S3 is subjected to airflow crushing, and the D50 is controlled to be 2-4μm.

[0074] The sodium source is at least one of sodium carbonate, sodium bicarbonate, sodium organic acid salts, and sodium phosphate;

[0075] The phosphorus source is at least one of phosphoric acid, sodium phosphate, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and iron phosphate.

[0076] The carbon source is preferably a water-soluble organic compound, and more preferably at least one of glucose, citric acid, starch, ascorbic acid, cyclodextrin, and polyethylene glycol.

[0077] Preferably, the weight ratio of the organic carbon source to the iron source is 1:10 to 20.

[0078] Example 1

[0079] The specific material in this embodiment is Na4Fe. 3-c M c (PO4)2P2O7, its preparation process is as follows:

[0080] S1: Preparation of Al-doped iron phosphate (M = Al):

[0081] Step (1) The raw materials aluminum sulfate (M source), ferrous sulfate, and phosphoric acid are dissolved in the reaction vessel at a molar ratio of 0.02:0.98:1;

[0082] (2) The pH value was adjusted to 2.0 by using alkaline solution and the reaction time was 4h to obtain iron phosphate precipitate, which contained trace metal element doping;

[0083] (3) The precipitate after filtration and washing was vacuum dried and then calcined at 500℃ (nitrogen atmosphere) for 4h to obtain aluminum-doped iron phosphate.

[0084] S2: Weigh 45g of aluminum-doped iron phosphate, sodium acetate, ammonium dihydrogen phosphate and glucose mixture obtained in S1, wherein the molar ratio of Na:(Fe+M):P is 4:3:4, and glucose is 10% of the weight of the doped iron phosphate. Dissolve in 500ml of water and stir to obtain suspension A.

[0085] S3: Transfer suspension A to a sand mill, mill at 2000 rpm for 1 hour, and then control the particle size to D50 < 300 nm.

[0086] S4: Spray dry the precursor solution of S3, controlling the outlet temperature at 100℃ and the flow rate at 35ml / min; to obtain spherical precursors;

[0087] S5: The precursor is transferred to a box furnace and calcined at 500°C for 10 hours in a nitrogen atmosphere to obtain carbon-coated sodium iron pyrophosphate.

[0088] S6: The gas flow obtained in S5 was broken up to control D50 to be less than 2 μm. Na4Fe based on Al front-end doping was thus prepared. 3-c M c(PO4)2P2O7 material.

[0089] Example 2

[0090] Compared with Example 1, the only difference is that the doping element M in step 1 of S1 is changed, specifically:

[0091] Group A: Element M is Ni, which accounts for 2% of the total molar amount of Fe+M;

[0092] Group B: Element M is Ti, which accounts for 1% of the total molar amount of Fe+M;

[0093] Group C: Element M is Al, which accounts for 3% of the total molar amount of Fe+M;

[0094] All other operations and parameters are the same as in Example 1.

[0095] Example 3

[0096] Compared with Example 1, the only difference is that in step (3) of S1, the calcination temperature is adjusted to 600°C and the time is 3h, while other conditions remain unchanged.

[0097] Example 4

[0098] Compared with Example 1, the only difference is that the pH value in step (2) of S1 is adjusted to 2.2, and the calcination temperature of S5 is 600℃ and the time is 6h, while other conditions remain unchanged.

[0099] Example 5

[0100] Compared with Example 1, the only difference is that in S1, in step 3, the calcination treatment is not performed, but the vacuum-dried material is directly used as the doped iron phosphate for subsequent processing.

[0101] Example 6

[0102] Compared with Example 1, the only difference is that in S1, in step 3, the vacuum-dried material is preheated at 350°C in a nitrogen atmosphere for 1 hour, and then calcined at 500°C in a nitrogen atmosphere for 3 hours to obtain the doped iron phosphate. Other operations and parameters are the same as in Example 1.

[0103] Comparative Example 1

[0104] Compared with Example 1, the only difference is that in step S1, the doping element is not included, but a single iron phosphate is used, and the iron content in the iron phosphate is the same as the iron + M element in the doped iron phosphate of Example 1. Other operations and parameters are the same as in Example 1.

[0105] Comparative Example 2

[0106] Compared with Example 1, the only difference is the back-end doping process, specifically: in step 1 of S1, aluminum sulfate is not added, but is added during the mixing process of S2. Other operations and parameters are the same as in Example 1.

[0107] Comparative Example 3

[0108] Compared with Example 1, the only difference is that a one-pot doping process is used. Specifically, step S1 is omitted, and instead, equal molar amounts of ferrous sulfate, ammonium phosphate and aluminum sulfate are added in S2. After mixing in one pot of liquid phase, subsequent steps are carried out. All other operations and parameters are the same as in Example 1.

[0109] Electrical performance tests were performed on the cathode materials prepared in each embodiment and comparative example:

[0110] The main steps of the test are as follows:

[0111] (1) Using a 2032 model battery case, the positive electrode is a positive electrode material sheet, the current collector is aluminum foil, the active material (the materials finally prepared in each example and comparative example) is: conductive carbon (acetylene black) : PVDF = 7: 2: 1, the negative electrode is sodium metal, and the battery is assembled using a fiber separator (model Whatman Grade GF / D) and an electrolyte of 1M NaPF6 (pure PC + 5% FEC).

[0112] (2) Set the resting time to 12 hours, set a charging program with a rate of 3C, a voltage range of 2.0V to 4.0V, a cycling temperature of room temperature or -10℃, and cycle 1000 times.

[0113] The test results are shown in Table 1:

[0114] Table 1

[0115]

[0116] As can be seen from the process of this invention, by using the pre-prepared doped iron phosphate as described in this invention, followed by subsequent sintering treatment, the problem of difficulty in successful doping caused by the low sintering temperature of iron phosphate pyrophosphate-based materials, as well as the problem of easy formation of impurity phases, can be unexpectedly solved, making it suitable for high-rate, low-temperature long-cycle application requirements.

Claims

1. A method for preparing iron-based phosphate cathode active materials by doping with iron phosphate, characterized in that, Iron phosphate doped with metal M was obtained in advance, and then it was compounded with other raw materials for synthesizing active materials and calcined to obtain the iron-based phosphate positive electrode active material. The metal M includes at least one of Ni, Ti, and Al; Metal M source, phosphoric acid source and iron source are co-precipitated and dried to obtain metal M-doped iron phosphate; the co-precipitated and dried material is thermally activated at a temperature of 450~700℃ to obtain metal M-doped iron phosphate. The other raw materials include a sodium source; the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium organic acid salts, and sodium phosphate. The chemical formula of the prepared iron-based phosphate positive electrode active material is Na. a Fe b M c (PO4) d (P2O7) e Where 0 < a < 5; 0 < b < 4; c is 0.01~0.05; 0 <d<4;0<e<4。 2. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 1, characterized in that, The metal source M and the iron source are water-soluble salts of their respective metal elements.

3. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 2, characterized in that, The metal M source and iron source are derived from at least one leachate from minerals containing the elements and waste battery cathode materials.

4. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 1, characterized in that, The phosphoric acid source is at least one of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate. In the metal source M, iron source, and phosphoric acid source, the molar ratio of (M+Fe) / P is 0.95~1:1, and the molar percentage of M / (M+Fe) is 0.1~5 mol%. The pH during the coprecipitation stage is 1-4.

5. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 1, characterized in that, The atmosphere for the thermal activation process is at least one of nitrogen and an inert gas; The heat activation treatment time is 1~6 hours.

6. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 1, characterized in that, The co-precipitated and dried material was pre-activated and then thermally activated to obtain the metal M-doped iron phosphate. The atmosphere during the pre-activation stage is at least one of nitrogen and an inert gas; The temperature during the pre-activation stage is 300~400℃; The pre-activation stage lasts for 1 to 2 hours.

7. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 1, characterized in that, The other raw materials may also include an added phosphorus source, which is at least one of phosphoric acid, sodium phosphate, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, disodium hydrogen phosphate, and sodium dihydrogen phosphate.

8. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 1, characterized in that, The other raw materials may also include carbon sources; The carbon source is a water-soluble organic compound.

9. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 8, characterized in that, The carbon source is at least one of glucose, citric acid, starch, ascorbic acid, cyclodextrin, and polyethylene glycol. The weight ratio of the carbon source to the metal M-doped iron phosphate is 5-15%.

10. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 8, characterized in that, The other raw materials may also include halogen sources.

11. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 1, characterized in that, The composite process can be either solid-phase composite or liquid-phase composite followed by solvent removal.

12. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 11, characterized in that, The solvent in the liquid phase composite stage is an aqueous solvent, which is a mixture of water and water-organic solvent. The liquid-phase recombination stage is carried out with mechanical assistance; The aforementioned mechanical auxiliary means is ball milling or sand milling; The solvent removal method is spraying.

13. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 1, characterized in that, The roasting stage is carried out in a protective atmosphere; The roasting temperature is 450~650℃; The roasting time at the roasting temperature is 4~14 hours.

14. The method for preparing iron-based phosphate cathode active materials by doping with iron phosphate as described in claim 13, characterized in that, The protective atmosphere includes at least one of nitrogen and an inert gas; The roasting temperature is 500~600℃; After roasting, the material is crushed. The fragmentation method is airflow fragmentation; The D50 of the crushed particles was controlled at 2~4μm.

15. A method for preparing iron-based phosphate cathode active material using doped iron phosphate obtained by any one of claims 1 to 13.

16. The iron-based phosphate positive electrode active material as described in claim 15, characterized in that, a is 2~4, b is 1~3, c is 0.01~0.05, and d+e=1~3.

17. The iron-based phosphate positive electrode active material as described in claim 16, characterized in that, The chemical formula of the iron-based phosphate positive electrode active material is: Na₄Fe 3-c M c (PO4)2P2O7, Na3Fe 2-c M c One or more of (PO4) and P2O7.

18. The application of the doped iron phosphate prepared by the preparation method according to any one of claims 1 to 13 in the preparation of iron-based phosphate cathode active materials, characterized in that, It is used as a positive electrode active material in the preparation of sodium-ion batteries.

19. A positive electrode for a sodium-ion battery, comprising a current collector and a positive electrode material composited on its surface, said positive electrode material comprising a positive electrode active material, characterized in that, The positive electrode active material comprises iron-based phosphate positive electrode active material prepared by any one of the preparation methods of claims 1 to 13, which is doped with iron phosphate.

20. The positive electrode of the sodium-ion battery as described in claim 19, characterized in that, In the aforementioned positive electrode active material, the content of the iron-based phosphate positive electrode active material is above 20 wt%; The content of the positive electrode active material in the positive electrode material is above 60 wt.%; The positive electrode material may also contain conductive agents and binders; The content of conductive agent and binder is below 15 wt.%.

21. The positive electrode of the sodium-ion battery as described in claim 20, characterized in that, In the aforementioned positive electrode active material, the content of the iron-based phosphate positive electrode active material is above 60 wt%; The content of the positive electrode active material in the positive electrode material is 70~90 wt.%; The content of conductive agent and binder is 5~10 wt.%.

22. A sodium-ion battery, comprising a cell and an electrolyte soaking the cell, wherein the cell comprises a positive electrode, a separator, and a negative electrode sequentially laminated together, characterized in that, The positive electrode described herein is the positive electrode according to any one of claims 19 to 21.

Citation Information

Patent Citations

  • Mg-doped fluorinated sodium ferric phosphate material for sodium-ion battery and preparation method of Mg-doped fluorinated sodium ferric phosphate material

    CN114725382A

  • Preparation method of ferrophosphorus sodium ore type ferric phosphate sodium composite material

    CN114956031A

  • Multiple ions co-doped lithium iron phosphate material and preparation method thereof

    CN105152155A

  • Preparation method and application of lithium iron phosphate positive electrode material

    CN114614011A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117393732A